THE INFLUENCE OF ONLINE LEARNING ON STUDENTS’ CHARACTERISTICS - Rudy Rudy; Widya Heseki Haraito Silalahi; Tuti Farida Sinaga (IdeBahasa, 2021)
During the pandemic time, almost all educational institutions implement online learning system for their students. This research aims at identifying the concept of online learning and analyzing the types of characteristics that can be formed through online learning. It is expected to contribute as a complement of theory in the fields of humanities, social sciences, and education. It can also be additional material for researchers who are interested in the topic of online learning. The data were obtained from the questionnaire responded by 22 students of the the 6th semester (morning class E) of FKIP UNPRI Medan and the reviewing of a number of relevant literature. As a conceptual analysis study, the data were analyzed by using representation theory to interpret the concept of online learning and its impact which could symbolize certain meanings. The result of analysis suggested that the term “online learning” can basically be conceptualized as a learning system emphasizing freedom which could show efficiency and innovation. The result of analysis also revealed that there were three types of characteristics – curiosity, facing challenges and a sense of responsibility that can be formed as a result of online line study which is considered to contribute to character building.